Comparing the outcomes of termination of second trimester pregnancy with a live fetus using intravaginal misoprostol between women with and without previous cesarean section - Saipin Pongsatha; Nuchanart Suntornlimsiri; Theera Tongsong (BMC, 2024)
Abstract Objective To compare the outcomes of termination of pregnancy with live fetuses in the second trimester (14-28 weeks), using misoprostol 400 mcg intravaginal every 6 h, between women with previous cesarean section (PCS) and no previous cesarean section (no PCS). Methods A comparative study was conducted on a prospective database of pregnancy termination in the second trimester, Chiang Mai university hospital. Inclusion criteria included: (1) singleton pregnancy; (2) gestational age between 14 and 28 weeks; and (3) pregnancy with a live fetus and medically indicated for termination. The participants were categorized into two groups; PCS and no PCS group. All were terminated using misoprostol 400 mcg intravaginal every 6 h. The main outcomes were induction to fetal delivery interval and success rate, defined as fetal delivery within 48 h. Results A total of 238 women, including 80 PCS and 158 no PCS, were recruited. The success rate of fetal delivery within 48 h between both groups was not significantly different (91.3% vs. 93.0%; p-value 0.622). The induction to fetal delivery interval were not significantly different (1531 vs. 1279 min; p-value > 0.05). Gestational age was an independent factor for the success rate and required dosage of misoprostol. The rates of most adverse effects of misoprostol were similar. One case (1.3%) in the PCS group developed uterine rupture during termination, ending up with safe and successful surgical removal and uterine repair. Conclusion Intravaginal misoprostol is highly effective for second trimester termination of pregnancy with PCS and those with no PCS, with similar success rate and induction to fetal delivery interval. Gestational age was an independent factor for the success rate and required dosage of misoprostol. Uterine rupture could occur in 1.3% of PCS, implying that high precaution must be taken for early detection and proper management. Synopsis Intravaginal misoprostol is highly effective for termination of second trimester pregnancy with a live fetus, with a comparable success rate between women with and without previous cesarean section, with a 1.3% risk of uterine rupture among women with previous cesarean section.